2021
DOI: 10.15448/1980-6108.2021.1.39425
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19, the anti-vaccine movement and immunization challenges in Brazil

Abstract: AIMS: The COVID-19 pandemic suddenly and significantly increased hospitalizations for pneumonia with systemic inflammatory disease. Since its appearance, COVID-19 has affected more than 200 countries, with more than 90 million cases and almost 2 million deaths. So far, there is no quality evidence regarding the specific pharmacological therapy for COVID-19; most treatments usually involve off-label use of existing drugs and have unproven efficacy. The global effort converges on the development of a vaccine; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Indeed, resistance to COVID-related mask and vaccine mandates and lockdowns—as well as criticism of public health experts—was strongest among populist-leaning politicians, at both the federal and provincial levels. Also, research has shown that distrust toward elites and experts is strong in both the vaccine hesitant and populists (Carvalho Bivar et al, 2021), helping to explain why individuals with stronger populist attitudes tend to be more hesitant about COVID-19 vaccines (Edwards et al, 2021). These findings align with previous research that has found that vaccine hesitancy is anchored in a broader anti-elite and anti-establishment worldview (Stoeckel et al, 2022).…”
Section: Populism Covid-19 and The People's Party Of Canadamentioning
confidence: 99%
“…Indeed, resistance to COVID-related mask and vaccine mandates and lockdowns—as well as criticism of public health experts—was strongest among populist-leaning politicians, at both the federal and provincial levels. Also, research has shown that distrust toward elites and experts is strong in both the vaccine hesitant and populists (Carvalho Bivar et al, 2021), helping to explain why individuals with stronger populist attitudes tend to be more hesitant about COVID-19 vaccines (Edwards et al, 2021). These findings align with previous research that has found that vaccine hesitancy is anchored in a broader anti-elite and anti-establishment worldview (Stoeckel et al, 2022).…”
Section: Populism Covid-19 and The People's Party Of Canadamentioning
confidence: 99%
“…Vaccine hesitancy matches flawlessly in populist agendas. Both share the profound distrust in elites and experts as their main drivers [ 45 ]. High levels of distrust and polarization are fertile areas for strengthening dissatisfaction against the elite [ 46 ].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…High levels of distrust and polarization are fruitful grounds for amplifying dissatisfaction with the elite [ 21 ]. Citizen’s feelings about vaccines depend on their perceptions regarding the competence and motivation of each of the components of the vaccines value chain (v.gr., the pharmaceutical business, investigators, and health professionals), i.e., the elite, in populist terms [ 22 ].…”
Section: Populism and Vaccinesmentioning
confidence: 99%